KENDALA GURU PAUD DALAM MENERAPKAN DAN MENGEMBANGKAN MATERI KURIKULUM MERDEKA - Hardianika Rahmaningtyas; Ida Wijayanti; Sumarno (STKIP Subang, 2024)
In the current era of Indonesian education, there are many challenges faced by early childhood educators in implementing the Independent Curriculum. These difficulties include the complexity of designing modules, determining competency indicators, and arranging interesting activities. Through a qualitative descriptive methodology that uses interview methods and document analysis, this research aims to gain insight from educators and administrators. These findings explain the efforts and challenges experienced by educators at the PAUD level in balancing structure and flexibility in teaching materials, establishing holistic competency indicators, and encouraging experiential learning. This research contributes to improving early childhood education practice by providing a deeper understanding of the barriers and opportunities in the context of the Merdeka Curriculum.